Teacher Strategic Management in Improving Student Learning Motivation in Madrasah Aliyah - Era Yunita; Budi Budi; Shahzadi Hina Sain (At-Ta'lim : Media Informasi Pendidikan Islam, 2025)
ENGLISH: Teacher Strategic Management in Improving Student Learning Motivation in Madrasah AliyahObjective: This study aims to understand the strategies used by teachers to improve student motivation at Madrasah Aliyah Swasta EX-PGA Proyek Univa Medan. Method: This study used a qualitative-descriptive method, with data collected through observation, interviews, and documentation and analyzed through a reduction process. Results: Teachers' Various management strategies in the teaching process can have a positive effect and produce good student results, especially at the Madrasah Aliyah level. This makes students more enthusiastic about learning, able to concentrate and perform satisfactorily. Conclusion: Teaching strategy management at the EX-PGA Private Senior High School, Univa Medan Project, enhances student learning motivation through the Problem-Based Learning (PBL) approach, with proper planning that encourages active participation, focus, and learning outcomes while considering individual student characteristics. Contribution: This study provides insights into the role of teachers' strategic management in enhancing students' learning motivation and recommends implementing innovative approaches, such as Problem-Based Learning, to improve educational quality.INDONESIAN: Manajemen Strategi Guru Dalam Meningkatkan Motivasi Belajar Siswa di Madrasah AliyahTujuan: Penelitian ini bertujuan untuk memahami pengelolaan strategi guru yang digunakan untuk meningkatkan motivasi belajar siswa di Madrasah Aliyah Swasta EX-PGA Proyek Univa Medan. Metode: Metode penelitian menggunakan kualitatif-deskriptif, data dikumpulkan melalui observasi, wawancara, dan dokumentasi, analisis data melalui proses reduksi. Hasil: Berbagai strategi manajemen yang digunakan oleh guru dalam proses pengajaran dapat memberikan efek positif dan hasil yang baik bagi siswa khususnya ditingkat Madrasah Aliyah. Hal ini membuat siswa lebih bersemangat dalam belajar, dapat berkonsentrasi, dan menunjukkan prestasi siswa yang memuaskan. Kesimpulan: Manajemen strategi pengajaran di Madrasah Aliyah Swasta EX-PGA Proyek Univa Medan meningkatkan motivasi belajar siswa melalui pendekatan Problem-Based Learning (PBL), dengan perencanaan yang baik yang mendorong partisipasi aktif, fokus, dan hasil belajar, serta memperhatikan ciri-ciri individu siswa. Kontribusi: Penelitian ini menyajikan informasi mengenai peran manajemen strategi guru dalam meningkatkan motivasi belajar siswa, serta merekomendasikan penerapan pendekatan inovatif seperti Pembelajaran Berbasis Masalah untuk meningkatkan mutu pendidikan.